2011
DOI: 10.1159/000324895
|View full text |Cite
|
Sign up to set email alerts
|

Pain Relief and Functional Recovery in Patients with Complex Regional Pain Syndrome after Motor Cortex Stimulation

Abstract: In addition to pain and neurovegetative symptoms, patients with severe forms of complex regional pain syndrome (CRPS) develop a broad range of symptoms, including sensory disturbances, motor impairment and dystonic posturing. While most patients respond to medical therapy, some are considered refractory and become surgical candidates. To date, the most commonly used surgical procedure for CRPS has been spinal cord stimulation. This therapy often leads to important analgesic effects, but no sensory or motor imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 51 publications
2
16
0
2
Order By: Relevance
“…We observed a significant association between burning (superficial) spontaneous pain relief and effective results (based on the VAS score) in our study; thus, we believe that the pain relief mediated by MCS is the result of orthodromic activation of the corticofugal pathways and antidromic activation of thalamocortical pathways, and the substantia gelatinosa, which participates in the modulation of the whole pain and the burning pain, plays an important role in these procedures. This is consistent with Fonoff’s research in animal models [26-28]. There are some limitations in our study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We observed a significant association between burning (superficial) spontaneous pain relief and effective results (based on the VAS score) in our study; thus, we believe that the pain relief mediated by MCS is the result of orthodromic activation of the corticofugal pathways and antidromic activation of thalamocortical pathways, and the substantia gelatinosa, which participates in the modulation of the whole pain and the burning pain, plays an important role in these procedures. This is consistent with Fonoff’s research in animal models [26-28]. There are some limitations in our study.…”
Section: Discussionsupporting
confidence: 93%
“…According to a study by Goto et al [25] using diffusion tensor imaging to examine the effectiveness of M1 rTMS for CPSP, preservation of thalamocortical and corticofugal motor tracts predicts treatment efficacy. In an animal model of neuropathic pain, Pagano et al [26] and Fonoff et al [27, 28] found that animals treated with MCS had a decrease in Fos and zif expression in the dorsal horn of the spinal cord (DHSC), and an increase in Fos and zif expression in the periaqueductal gray matter. The periaqueductal gray matter is a part of a descending pain suppressor pathway that projects to the DHSC via the rostral ventromedial medulla.…”
Section: Discussionmentioning
confidence: 99%
“…[118119120] In the worldwide literature, there is a growing interest on stimulation of the motor cortex for treatment of FCNP [Figure 1]. [96] Initially tried for thalamic pain, it has been tried for many treatment-resistant pain syndromes [54] such as phantom limb pain, [95101106] postherpetic neuralgia, brachial plexus avulsion, [57] poststroke pain, [324648505176106111] Wallenberg syndrome,[3349] complex regional pain syndrome, [2770108] pain secondary to multiple sclerosis, [112] spinal cord injury pain, [88113] and posttraumatic brain injury pain. [107] Recently, MCS has also been tried in other nonpainful conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Motor cortex stimulation (MCS) is considered promising, especially to treat trigeminal NP and post-stroke central pain syndromes, such as thalamic pain and brachial plexus avulsion, among others 21,[61][62][63] . Most studies involving MCS focuses on post-stroke and atypical trigeminal neuropathy, for which there are few effective treatments.…”
Section: Motor Cortex Electrical Stimulationmentioning
confidence: 99%
“…MCS results for trigeminal NP are very interesting, because they show that 75% to 100% of patients have obtained good to excellent pain relief. Other groups have also shown pain improvement in less studied syndromes, such as complex regional pain syndrome, with encouraging results in very severely ill patients with therapeutic failure to spinal cord stimulation [61][62][63] . Motor cortex stimulation effect depends on electrodes implant target, which apparently should be implanted in motor cortex region corresponding to body segment affected by pain.…”
Section: Motor Cortex Electrical Stimulationmentioning
confidence: 99%